IMPLEMENTASI METODE TALAQQI DALAM AKSELERASI KEMAMPUAN MEMBACA AL-QUR’AN DI DESA ARA PAYUNG, KEC. PANTAI CERMIN, KAB. SERDANG BEDAGAI - Ilham Tumanggor Tumanggor; Muhammad Syarif Muda Hasibuan; Andi Andi; Candra Gunawan (ASSUNNAH PRESS, 2026)
The ability to recite the Qur'ān in accordance with proper tajwīd rules constitutes an essential dimension of religious literacy for Muslim communities. Preliminary observation in Ara Payung Village, Pantai Cermin Subdistrict, Serdang Bedagai Regency, identified persistent challenges in Qur'ānic recitation among adult women, particularly concerning the articulation points of the letters (makhārij al-ḥurūf), basic tajwīd rules, and fluency in reciting Sūrat al-Fātiḥah. This community engagement program sought to accelerate participants' Qur'ānic reading competence through the talaqqi method, framed within a service-learning pedagogy. Twenty adult women participants engaged in thirteen structured halaqah sessions over a period of fourteen days. Data were gathered through participant observation and pre- and post-program assessments using a four-criterion rubric covering articulation accuracy, application of basic tajwīd, correctness of vowel length (mad), and reading fluency. Findings indicate that the number of participants attaining the